ENHANCING EDUCATIONAL IMPACT THROUGH ACTIVE TEACHING METHODS - Xamrozoda Zarinai Mirzo-Ulug‘bek. (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
Active teaching methods enhance both the developmental and educational outcomes of learning by fostering student participation, open dialogue, and independent thinking. These approaches promote critical and creative thinking, strengthen communication and teamwork, and help students build professional competencies. Moreover, active learning increases motivation, encourages responsibility for learning, and prepares students for real-world professional challenges.